The Essence Of Faith: Diverse Perspectives and Islamic Views - Abdumtalievich, Omarov Nurseit (Indonesian Journal Publisher, 2024)
There are various views on the nature of faith (Iman). One perspective, held by the Khawarij, suggests that faith is merely the affirmation of obedience and disobedience; they argue that a person who sins is considered a non-believer, and only their obedience is seen as a confirmation of their faith. On the other hand, the Mutazilites believe that faith is a combination of belief and deeds, emphasizing that faith is established both by words and actions. They assert that belief in the heart is crucial, while external actions only complement the inner belief. Other theological schools, like the Najjarites and Karramiyyah, focus on the importance of verbal declaration and belief in the heart, differentiating between a person’s inner faith and outward affirmation. The Ahl al-Sunnah's view aligns with the understanding that faith is the inner affirmation in the heart, and verbal affirmation is essential for recognizing someone as a believer in the worldly context. According to the Sighnī (author), the true nature of faith is rooted in the heart's confirmation and the verbal declaration, which ensures the preservation of a person's life and property in this world. However, they clarify that one's faith is not based solely on deeds or verbal expressions but is a matter of sincere internal belief.